Secondary Students’ Engagement in Jigsaw Method-Asissted Vocabulary Learning - Dayem, Dayem; Pahlevi, Muhammad Reza; Ambarwati, Evi Karlina (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2023)
This study aims to determine the involvement of students in learning vocabulary using the jigsaw method. This research belongs to the type of descriptive qualitative research. The subjects in this study were students of class VIII A of SMPN 2 Telagasari, totaling 32 students. This study uses observation, interviews, and documentation to collect data. Observations were made for two meetings, then interviews were conducted to determine the involvement of students in learning vocabulary using the jigsaw method. The results of this study indicate that a) group discussion session of jigsaw involves students' to learn vocabulary interactively (Cognitive Engagement). All participants stated that the jigsaw method helped students to learn vocabulary well and discussions with friends helped them in learning, then students are also interested in asking questions during the learning process. b) exchange expert group students' in a team motivate members to do task (Behavior Engagement) it can be seen from the results of observations and interviews that have been carried out that students are motivated to work on vocabulary assignments because they interact more with friends during vocabulary learning. c) jigsaw method attracts students' enthusiasm in vocabulary learning (Emotional Engagement) it can be seen from the results of observations and interviews that have been done that students like to learn vocabulary using the jigsaw method on the grounds that the jigsaw method is fun and easy.